2017
DOI: 10.3389/fmicb.2017.00211
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Redox Transformations of Iron, Copper, and Chromium Catalyzed by Extremely Acidophilic Bacteria

Abstract: Experiments were carried out to examine redox transformations of copper and chromium by acidophilic bacteria (Acidithiobacillus, Leptospirillum, and Acidiphilium), and also of iron (III) reduction by Acidithiobacillus spp. under aerobic conditions. Reduction of iron (III) was found with all five species of Acidithiobacillus tested, grown aerobically on elemental sulfur. Cultures maintained at pH 1.0 for protracted periods displayed increasing propensity for aerobic iron (III) reduction, which was observed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 42 publications
2
47
0
Order By: Relevance
“…While it has long been known that A. thiooxidans can reduce ferric iron [27], later work showed that this acidophile cannot grow by ferric iron respiration [28]. Reduction of ferric iron in aerobically grown cultures has been shown to be widespread amongst the acidithiobacilli [29], and ongoing reduction of soluble ferric iron by Acidithiobacillus caldus has recently been shown to sustain the growth of Leptospirillum ferriphilum in mixed cultures [30]. The fact that ferric iron can be reduced under aerobic conditions extends the potential for the bioprocessing of minerals such as goethite.…”
Section: Discussionmentioning
confidence: 99%
“…While it has long been known that A. thiooxidans can reduce ferric iron [27], later work showed that this acidophile cannot grow by ferric iron respiration [28]. Reduction of ferric iron in aerobically grown cultures has been shown to be widespread amongst the acidithiobacilli [29], and ongoing reduction of soluble ferric iron by Acidithiobacillus caldus has recently been shown to sustain the growth of Leptospirillum ferriphilum in mixed cultures [30]. The fact that ferric iron can be reduced under aerobic conditions extends the potential for the bioprocessing of minerals such as goethite.…”
Section: Discussionmentioning
confidence: 99%
“…The direct relationship observed between microbial aggregates and covellite in the cementation zone of the Las Cruces deposit and the in situ detection of abundant sulfatereducing bacteria strongly suggest that the current formation of the high-grade copper mineralization is controlled by microbial metabolism, with the covellite precipitating due to the increase of microbially mediated reduced sulfur. Precipitation of the copper sulfides also requires aqueous copper to be reduced from Cu 2+ to Cu + , a process that could be biologically mediated by some chemolithotrophic gammaproteobacteria related to Acidithiobacillus ferrooxidans at low pH under aerobic conditions (Johnson et al, 2017). Alternatively, in anaerobic environments, aqueous Fe 2+ is a rapid abiogenic reductant for copper under highly variable conditions (Matocha et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The online version of this article (https ://doi.org/10.1007/s0079 2-020-01157 -1) contains supplementary material, which is available to authorized users. growth by ferric iron respiration appears to be restricted to those species that also oxidize iron (Hallberg et al 2001;Johnson et al 2017). Some acidithiobacilli can also use hydrogen as sole electron donor, but while this appears to be a common trait for all strains of some species (A. ferrooxidans and A. ferridurans) this is not the case for strains of other species (A. ferrivorans, A. thiooxidans and A. caldus) and has not been observed in any strain of A. ferriphilus (Hedrich and Johnson 2013b;Falagán and Johnson 2016).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%